Gadflies and Zip Guns Mass Culture Criticism and Juvenile Delinquent Texts in America, 1945–1960 - Soiseth, Neil (Université d'Ottawa / University of Ottawa, 2016)
This study considers the analyses of diverse social and cultural critics in America in the late 1940s and 1950s. In particular, it examines their mostly jaundiced view of what they called mass culture and its related expressions. But where these intellectuals approached contemporary life with variations of skepticism and dread, this study argues that they suffered a myopia that inhibited their ability to see the so-called culture industries of postwar America as dynamic and engaging, not dominating and demeaning. To contextualize that skewed perspective, this study examines the postwar paperback industry and reconfiguring film business before delving into a specific form of mass culture, the juvenile delinquent text. The 1950s was a period of great concern about the status of teenagers within larger society. This anxiety gave birth to sociological studies offering diverse theories and true crime accounts of alienated and barbaric teenagers threatening civic virtue and the nation’s future. More importantly, it also spawned waves of novels and films devoted to both sympathetic accounts of juvenile delinquents and sensationalist tales that exploited the public’s fears and fascination. This study uses these texts to examine three topics that also worried intellectuals of the period—urban decline and suburban migration; a reconfiguration of masculinity; and the morality of a society predicated on consumption—and finds considerable overlap in the questions and analyses each pursued. Apart from making the case for widespread circulation of critical ideas in 1950s America, it argues for considerable ideological unsettledness and suggests an unacknowledged conversation of sorts between producers of mass culture and the intellectuals who treated such forms as evidence of dissenting art’s fatal decline. The stratification and segregation employed by cultural critics of the 1950s serves as a warning to contemporary scholars about the dangers in privileging high over low.
Keywords: mass; culture; juvenile; delinquency; paperbacks; film; intellectuals; criticism; 1950s; 1940s; United; States; teenagers; America